Investigation of the three-dimensional flow field for proton exchange membrane fuel cell with additive manufactured stainless steel bipolar plates: Numerical simulation and experiments. (15th April 2023) - Zhang, Jian; Huang, Pengyi; Ding, Honghui; Xin, Dongqun; Sun, Shufeng
Abstract: A bipolar plate with a complex three-dimensional (3D) flow field structure could bring better performance of proton exchange membrane fuel cell (PEMFC). In this paper, three types of 3D flow field bipolar plates with different porosity (M1, M2 and M3) and a conventional two-dimensional (2D) serpentine flow field bipolar plate (SP), were fabricated using selective laser melting (SLM). The forming quality of the bipolar plate was determined. The distribution characteristics of current density, oxygen, water content and temperature in different flow field structures and their effects on the performance of PEMFC were analyzed by numerical simulation. By using T 3 -100 cell test system and MTS exceeded E44 electronic universal test system, the polarization test and contact resistance test were conducted on the conventional SP bipolar plate and the M3 bipolar plate. Results show that the different bipolar plates prepared by the SLM process exhibit high forming quality, and the forming error for the 3D flow field bipolar plates is less than 4%. The M3 flow field exhibits the best capabilities for heat and mass transfer and water management. The M3 flow field produces a maximum power density of 0.547 W/cm 2, which is 8.96% higher than that of the SP flow field. This is attributed to the more uniform distribution of gas and liquid in the M3 flow field as well as the lower contact resistance. Graphical abstract: Image 1 Highlights: Stainless steel 3D flow field bipolar plates (M1, M2, M3) and a serpentine flow field bipolar plates (SP) were fabricated by SLM. The bipolar plate formed by SLM has high quality, such as low surface roughness and small dimension error. The polarization test and the CFD results show that the performance of the M3 fuel cell is better than that of the SP.